Highly Aggressive Intraparenchymal Solitary Fibrous Tumor of the Lung with Distant Metastasis: A Case Report and Review of CT and PET/CT Findings - Jeong Joo Woo; Jin Kyung An (Reports)
Background and Clinical Significance: Solitary fibrous tumors (SFTs) arising from the lung parenchyma without any relation to the pleura are rare. Case Presentation: We report a case of highly aggressive intraparenchymal SFT of the lung in a 52-year-old woman with rapid distant metastasis to the brain, lungs, and bones within one year post-operation. Chest computed tomography (CT) showed a 5.5 cm-sized, round, but partially lobulated mass with ambiguous enhancement in the right upper lobe. Positron emission tomography/computed tomography (PET/CT) demonstrated strong homogeneous FDG uptake. Unfortunately, the patient succumbed to the disease within one year of diagnosis. Conclusions: Among intrapulmonary SFT, the cellular variant may appear as a cystic mass due to accompanying hemorrhage, coagulation necrosis, and myxoid degeneration. In the absence of mediastinal metastatic adenopathy, it can be mistaken for a benign cystic mass, making PET/CT findings a crucial tool for suggesting a malignancy. Furthermore, as cellular-type intrapulmonary SFT can exhibit aggressive distant metastasis, understanding the CT and PET/CT findings in this condition is essential for accurate diagnosis and treatment planning.